2010
DOI: 10.3382/ps.2009-00136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waterbath stunning on the electroencephalograms and physical reflexes of broilers using a pulsed direct current

Abstract: Stunning efficiency of a pulsed direct current was assessed regarding the effect on the electroencephalogram (EEG) and physical reflexes. Four hundred sixty-seven broilers (males and females) were stunned in an electrified waterbath with 60, 80, 100, 120, and 150 mA at frequencies of 70, 100, 200, 400, 800, and 1,500 Hz. Stunning time was 10 s. The EEG recordings lasted for 120 s poststun and simultaneously the occurrence of breathing, spontaneous eye blinking, corneal reflex, and wing flapping was recorded. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 10 publications
0
28
2
1
Order By: Relevance
“…Pulsed DC, on the other hand, only resulted in a maximum of 40% wing flapping for the highest stunning voltage of 120 V (Figure 3). This level is slightly lower compared with a previous study on pulsed DC stunning of 10 s (Prinz et al, 2010b). It can moreover be observed that the level of wing flapping was higher in females in the present study (Figure 3).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Pulsed DC, on the other hand, only resulted in a maximum of 40% wing flapping for the highest stunning voltage of 120 V (Figure 3). This level is slightly lower compared with a previous study on pulsed DC stunning of 10 s (Prinz et al, 2010b). It can moreover be observed that the level of wing flapping was higher in females in the present study (Figure 3).…”
Section: Discussioncontrasting
confidence: 81%
“…In their study, a pulsed DC of 70 Hz rendered more than 90% of broilers unconscious with minimum currents of 80 mA. The distinction might be caused by the longer stunning time of 10 s (Prinz, 2009;Prinz et al, 2010b). This might have caused a longer duration of insensibility in the broilers than 4 s of stunning time in the present study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The power in this band is recognized as expressing vigilance and the ability to experience sensory perceptions, including pain, whereas the lack of activity in this band is interpreted as an unequivocal loss of sensibility [6], [7], [8]. The power of the post decapitation EEG in this cognitive band has a time course comparable with the power in the 1–100 Hz band, but the time to half-life is shorter: 3.7 seconds, with a 95% confidence interval between 3.5 to 4.1 seconds (significantly different from the previous 5.5 seconds, t(2)  = 173, p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…With DC currents, the corneal reflex was not a reliable indicator of unconsciousness and insensibility at any current or frequency. Overall, these observations show that the presence or absence of a corneal reflex is not a reliable indicator of unconsciousness and insensibility, The recovery of corneal reflexes after stunning, together with the return of spontaneous breathing and eye blinking, can be signs of a progressive recovery of brain function (Wenzlawowicz and von Holleben, 2001;Prinz et al, 2010a). On the other hand, a continuing absence of a corneal reflex could be an indicator for approaching brain death or severe brain impairment (Gregory, 1989).…”
Section: Discussionmentioning
confidence: 99%